TI_GERICHTE 36.2005.10 vom 14. November 2005 , Sospensione degli obblighi dell'assicuratore e rescissione del contratto. - TI Tribunale d'appello (2005)
Sospensione degli obblighi dell'assicuratore e rescissione del contratto.